Engineering Dielectric Transition and Surface Polarity in Hydrothermally Synthesized MXene-PbO-PANI Nanocomposites - Demirelli, Kadir; Ercan, Cemile; Erol, İbrahim; Yakuphanoğlu, Fahrettin (Springer/Plenum Publishers, 2026)
In this study, Ti(3)C(2)Tx MXene-based nanocomposites were synthesized via hydrothermal-assisted in situ polymerization with polyaniline (PANI) and lead oxide (PbO), offering a novel approach to tune the dielectric transition behavior and surface polarity. Three different hybrid structures were prepared and characterized in detail: Ti(3)C(2)Tx MXene/PANI, Ti(3)C(2)Tx MXene(0).(18):PbO, and Ti(3)C(2)Tx MXene(0).(03):PbO0.(86):PANI(0).(11). XRD and SEM-EDX analyses confirmed the presence of alpha-PbO and beta-PbO phases and the homogeneous distribution of MXene layers. At the same time, AFM results showed a reduction in surface roughness after hybrid formation. According to contact angle measurements, pure PANI showed the highest hydrophilic behavior (38.0 degrees), while the MXene(0).(18):PbO system exhibited weaker hydrophilicity (67.6 degrees), and the MXene: PbO: PANI hybrid showed moderate wettability (49.7 degrees). Dielectric measurements performed over the frequency range of 200 Hz-10 MHz and the temperature range of 30-140 degrees C revealed two distinct polarization mechanisms. The MXene(0).(18):PbO system showed a negative dielectric constant and a DC conductivity value of 35 mS cm(-)& sup1; due to its metallic character. At the same time, the MXene: PbO: PANI hybrid exhibited positive dielectric behavior due to temperature-activated dipole orientation and a DC conductivity value of 140 nS cm(-)& sup1; at 50 degrees C. The results show that varying composition ratios and structural arrangements can precisely adjust dielectric properties, conductivity, and surface polarity. With these properties, the developed MXene-based nanocomposites stand out as strong candidate materials for capacitive systems, sensor applications, and energy-efficient electronic components. [GRAPHICS]
Keywords: MXene Contact Angle; PbO; Dielectric Properties; PANI; Hydrothermal